Movimiento de objetos por lectura de barras - Lata García, Juan Carlos (2011)
The Robot Arm Scorbot-ER 4u has been used to place cookie boxes through the reading of barcodes in the packing. To make this project, we used all the skills learned on our studies to choose the components as robot accessories, detectors and a power supply. The software used is Scorbase that was learned during the seminary to its application on this project. The priority of this project is avoid diseases of occupational health, decrease wasted time from mistakes, fatigue and rapiditying on the implementation of process.